Developments and Research Trends in Psycholinguistics in Arabic Language Learning: A Systematic Literature Review - Muhammad Hidayatullah; Moch. Fajarul Falah (Postgraduate Program of the State Islamic Institute of Palopo, 2026)
This study aims to analyze the developments and research trends in psycholinguistics within Arabic language learning through a Systematic Literature Review (SLR) approach. The review examines scholarly publications related to Arabic language acquisition, cognitive processes, affective factors, instructional strategies, social learning environments, and technological integration in Arabic language education. Data were collected from relevant academic publications and analyzed using thematic synthesis to identify publication characteristics, dominant research themes, and their implications for Arabic language learning development. The findings reveal that psycholinguistic research in Arabic language learning has developed into an increasingly dynamic and interdisciplinary field. The dominant themes identified include language acquisition, cognitive processing, learning theories, affective factors, social environment, and communicative instructional strategies. The review indicates that successful Arabic language learning is not solely determined by vocabulary mastery and grammatical competence but is also strongly influenced by learners’ cognitive readiness, emotional conditions, social interactions, and opportunities for meaningful communication. Furthermore, recent research trends demonstrate growing attention to learner-centered approaches, communicative learning, psychologically supportive environments, and technology-enhanced instruction. This study highlights the importance of designing adaptive and integrated Arabic language learning that accommodates learners’ cognitive, affective, and social characteristics. Future studies are recommended to strengthen empirical evidence through experimental, quantitative, mixed-method, and longitudinal research designs to examine the influence of psycholinguistic factors on Arabic language learning outcomes more comprehensively